The economics of disability and the discourse of eliminating inequalities and providing equal opportunities - WLAZŁO, MARCIN (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Marcin Wlazło, The economics of disability and the dis-course of eliminating inequalities and providing equal opportunities. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 33-53. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.02 Disability results in certain economic consequences, which are analysed mainly because of the generation of cost. The economic situation of people with disabilities and their families is usually associated with negative effects of neoliberalism, or causing and strengthening social inequality and excluding people unattractive on the market. In this context, the relationship between technological progress, economic growth and diagnostic and therapeutic services are also analysed. The article presents various aspects of the economic discourse focused on disability. The analysis is based on examples that consolidate the traditional image of disability as a factor affecting low economic status, through a description of the market of services and goods for people with disabilities, to examples of economic success achieved by people with disabilities.